COMPANY BOARDS AND THEIR IMPACT ON CORPORATE GOVERNANCE: EMPIRICAL EVIDENCE FROM INDIA & SINGAPORE (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Corporate Governance has taken center stage  in the last few decades in developed as well as  developing economies. Corporate Governance  is the guiding principle, which determines how  companies should be managed to take care of  all its stakeholders. Governance of any company  is primarily entrusted on its Board of Directors  (BODs) or The Board. The main objective of  this paper is to study the state of Corporate  Governance in India and Singapore, with special  emphasis on Corporate Governance aspects  related to Boards. A customized questionnaire  was deployed to collect primary data for the  analysis. The findings reported in the paper are  based on analysis conducted on empirical data  collected from selected corporate executives from  both countries, from diverse industrial segments.  Descriptive statistics has been used to present the  perception of the participants concerning the  proliferation of the corporate governance code  parameters related to Board of directors, in the  companies across India and Singapore. The study  observed that the proliferation of corporate  governance codes parameters related to Board  of Directors, in the companies across India  and Singapore significantly differed in terms  of board composition, board development,  accountability of the board of directors,  remuneration committee, audit committee,  risk assessment committee, CSR committee.  However, there are still some gaps that need to  be bridged.
Keywords: Corporate Governance; Stakeholders; Board of Directors; India; Singapore